Avaliação do efeito da melatonina sobre os tecidos periodontais de ratos com periodontite induzida experimentalmente - Santos, Bianca Caroline Custodio dos (2020)
Melatonin is a hormone that exerts the immunological, antioxidant, and anti-inflammatory effects. These effects can be beneficial in the treatment of specific dental diseases. They can be used therapeutically, for example, in lesions of the oral cavity of mechanical, bacterial, fungal, or viral origin, in post- surgical wounds caused by tooth extractions and other oral surgeries. As a result, the study aimed to evaluate the effects of melatonin on the periodontal tissues of rats, whether or not associated with ligature-induced periodontal disease. For this study, 40 male Wistar rats at eight weeks were randomized, initially divided into four groups, and submitted to intraperitoneal anesthesia. Two groups had induced periodontal disease for 30 days, favoring the accumulation of bacterial plaque and, consequently, the development of the periodontal disease. After induction, groups were formed with ten animals per group: Control Group (GCON), Ligature Group (GLIG), Melatonin Group (GMEL), and Ligature and Melatonin Group (GLIG-MEL). After 16 days with the ligature, 10 mg/kg of melatonin was administered orally for 14 days in the melatonin groups, and after the total 30 days of experimentation, the animals were euthanized. Then, the hemi-mandibles were dissected, which were submitted to histological, radiographic, and morphometric analyzes of the gingiva and bone. The results showed a significantly lower alveolar bone loss (p <0.05) in the animals that received the administration of melatonin, in which it had a prophylactic function against the effects of the disease, evidenced in radiographic, histomorphometric and histological analyzes in the bone cell count. Thus, it can be concluded that melatonin therapy promotes a protective effect on the bone tissue of rats with experimentally induced periodontitis.